2009
DOI: 10.1016/j.aquaculture.2009.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Co-feeding of live feed and inert diet from first-feeding affects Artemia lipid digestibility and retention in Senegalese sole (Solea senegalensis) larvae

Abstract: The present study intended to evaluate the effects of early introduction of inert diet in lipid digestibility and metabolism of sole, while larval feed intake, growth and survival were also monitored. Solea senegalensis larvae were reared on a standard live feed regime (ST) and co-feeding regime with inert diet (Art R). Trials using sole larvae fed with Artemia enriched with two different lipid emulsions, containing glycerol tri [1-, were performed at 9 and 17 days after hatching (DAH) to study lipid utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Assuming that lipid digestibility is high in Senegalese sole post-larvae, especially that of LC-PUFA Mai et al 2009), the identification of the preferential metabolic fate of fatty acids should be possible by comparing fish fatty acid profiles with those presented in the diets. Delta values for C18 fatty acids, like OLA and particularly ALA, provide indication that these were preferentially metabolized, likely for energy production purposes through b-oxidation, as observed in various fish species (Bell et al 2001;Tocher 2003;Morais et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that lipid digestibility is high in Senegalese sole post-larvae, especially that of LC-PUFA Mai et al 2009), the identification of the preferential metabolic fate of fatty acids should be possible by comparing fish fatty acid profiles with those presented in the diets. Delta values for C18 fatty acids, like OLA and particularly ALA, provide indication that these were preferentially metabolized, likely for energy production purposes through b-oxidation, as observed in various fish species (Bell et al 2001;Tocher 2003;Morais et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Larval rearing depends greatly on live feed supply, and various studies during these life stages have focused on weaning strategies (Engrola et al 2009a(Engrola et al , b, 2010Mai et al 2009). In hatcheries, during metamorphosis, it is common practice to gradually replace live feed with frozen Artemia metanauplii, generally enriched in lipids.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of different species are fed on Artemia sp. nauplii to adapt or optimize the digestion process, which may involve a gradual transition period of co-feeding with live feed and inert feed or an abrupt transition between the two forms of feeding (Ballagh, Fielder & Pankhurst, 2010;Bonaldo, Parma, Badiani, Serratore, & Gatta, 2011;Chepkirui-Boit et al 2011;Engrola et al, 2009;Mai et al, 2009). The index of larvae survival in current experimental conditions was 55%, which suggests that the supply of Artemia sp.…”
Section: Resultsmentioning
confidence: 89%
“…However, in sole co-fed a high Artemia replacement level (58% of total diet) both Artemia protein digestibility and retention efficiency decreased between 6 and 15 DAH (Engrola et al 2009b). Concerning lipid utilisation, Mai et al (2009) observed that Artemia replacement strategy in Senegalese sole has a toll in terms of growth and lipid digestibility but does not seem to compromise lipid metabolic utilisation. Lipid Fish Physiol Biochem (2010) 36:1-16 3 retention efficiency before metamorphosis was higher in co-fed sole, reaching values of 50%, while these values almost doubled during metamorphosis climax, ranging up to 80%.…”
Section: Tube-feedingmentioning
confidence: 88%